Chrome spinel in normal MORB‐type greenstones from the Paleozoic–Mesozoic Mino terrane, East Takayama area, central Japan: Crystallization course with a U‐turn. (March 2014) - Agata, Takashi; Adachi, Mamoru
Abstract Phenocrystic chrome spinel crystallized in normal MORB‐type greenstones in the East Takayama area. Associated phenocryst minerals show a crystallization sequence that was olivine first, followed by plagioclase, and finally clinopyroxene. Chrome spinel ranges from 0.54 to 0.77 in Mg/(Mg+Fe2+) and 0.21 to 0.53 in Cr/(Cr+Al); the Fe3+ content varies from 0.07 to 0.22 p.f.u. (O = 4). Significant compositional differences of spinel were observed among the phenocryst mineral assemblages. Chrome spinel in the olivine–spinel assemblage shows a wide range in Cr/(Cr+Al), and is depleted in Fe2+ and Fe3+. Chrome spinel in the olivine–plagioclase–clinopyroxene–spinel assemblage is Fe2+‐ and Fe3+‐rich at relatively high Cr/(Cr+Al) ratios. Basalt with the olivine–plagioclase–spinel assemblage contains both aluminous spinel and Fe2+‐ and Fe3+‐rich spinel. The assumed olivine–spinel equilibrium suggests that chrome spinel in the olivine–spinel assemblage changed in composition from Cr‐ and Fe2+‐rich to Al‐ and Mg‐rich with the progress of fractional crystallization. Chrome spinel in the olivine–plagioclase–clinopyroxene–spinel assemblage, on the other hand, exhibits the reversed variations in Mg/(Mg+Fe2+) and in Cr/(Cr+Al) ratios that decrease and increase with the fractional crystallization, respectively. The entire crystallization course of chrome spinel, projected onto the Mg/(Mg+Fe2+)–Cr/(Cr+Al) diagram, exhibits a U‐turn, and appears to be set on a double‐lane route. The U‐turn point lies in the compositional field of chrome spinel in the olivine–plagioclase–spinel assemblage, and may be explained by plagioclase fractionation that began during the formation of the olivine–plagioclase–spinel assemblage.